Report on learning in the Lower Kafue Multistakeholder Platform in Zambia: addressing gender, social inclusion and power dynamics - Ng’ambi, F.; Mapedza, Everisto D.; Buisson, Marie-Charlotte; Siangulube, F. S.; Kasoma-Pele, Winnie (2024)
This report examines the integration of gender equality, social inclusion, and power dynamics within the Multistakeholder Platform (MSP) for the Lower Kafue Basin in Zambia, launched on October 3, 2023. The MSP is part of the broader Resilient Aquatic Food Systems (AqFS) initiative, particularly under Work Package 3 – Aqua Plans, which aims to strengthen the inclusion of aquatic food systems within the cross-sectoral land-water-foodscape nexus. This initiative is pivotal in advancing sustainable development and resilience in the Lower Kafue Basin by ensuring that aquatic food systems are fully integrated into land and water management discussions. This study is significant because integrating gender equality, social inclusion, and addressing power imbalances are crucial for the MSP to achieve its broader objectives. By ensuring that all stakeholders, especially marginalized groups like women and rural communities, are included in decision-making, the MSP can promote more equitable and sustainable outcomes. These elements are key to creating a platform that is truly representative of all stakeholders in the basin. The study employed a mixed-methods approach, drawing on key informant interviews, observations from multiple MSP workshops, and a literature review. These three methods complemented each other and provided an in-depth analysis of how gender and power asymmetries play out within the MSP and how stakeholders engage within the platform and its activities. The data collected from these sources provides critical insights into both the successes and challenges faced by the MSP in promoting inclusive decision-making. The findings reveal that language barriers have been a significant obstacle to inclusive participation, particularly for community members, hindering their ability to engage effectively. However, the MSP has made notable progress in promoting inclusivity by intentionally creating a platform where all stakeholders can contribute to discussions. This has been achieved by encouraging the use of multiple languages and organizing stakeholders into working groups, ensuring broader and more effective participation across diverse groups. Another key finding was that some stakeholders felt the MSP could benefit from greater inclusion of community members, noting that there was an overrepresentation of government institutions in the platform. The findings underscore the need for continuous monitoring, targeted capacity-building, and the mainstreaming of gender equity to ensure that the MSP effectively serves all stakeholders, particularly marginalized groups.